Wybrane zagadnienia cywilnoprawne projektu ustawy o prywatyzacji przedsiębiorstw państwowych (z uwzględnieniem postanowień paktu o przedsiębiorstwie) - Szlęzak, Andrzej (Wydział Prawa i Administracji UAM, 1993)
The article presents the new draft of the Privatization Law. The author analyses the draft from t h e perspective of theoretical and practical problems connected with the privatization of the state sector. Besides, the author identifies potential areas of difficulties in implementing the provisions of the draft Law, and proposes the ways to eliminate the shortcomings of the proposed legislation.
Selected civil-law problems of the draft privatization law